SYSTEM FOR CATALYTIC REACTION - LEININGER, THOMAS FREDERICK (2014)
SYSTEM FOR CATALYTIC REACTION A system includes a reactor-adsorber configured to receive a gas, a regenerator configured to receive a saturated CO 2 adsorption material from the reactor-adsorber, a first solids pressurizing feeder configured to convey the saturated CO 2 adsorption material from the reactor-adsorber to the regenerator, and a second solids pressurizing feeder configured to convey a regenerated CO2 adsorption material from the regenerator to the reactor-adsorber. The reactor-adsorber includes a catalyst material configured to catalyze a water gas shift reaction of the gas to generate a hydrogen-rich gas, and a CO 2 adsorption material configured to adsorb CO 2 from the hydrogen-rich gas to generate the saturated CO 2 adsorption material. The regenerator is configured to regenerate the saturated CO 2 adsorption material to provide the regenerated CO 2 adsorption material and CO 2. The first and second solids pressurizing feeders are configured to at least substantially reduce or prevent fluid flow between the reactor-adsorber and the regenerator. -10 20: 24 32 349 202:: FIRST 320 -" SECOND REACTOR 12 16 REACTOR 14 '36 54 132 122 12414 50 3102 128 60 126 1414214 9 100 134 148 596 58 130 136 98 104 12 150 154 94 56 62 106 1218 94108 64 1 138 28 88- 90 38 28 110 O 120 84- 7610 -78 72- 70